Studies on Dyeing Performance of Novel Acid Azo Dyes and Mordent Acid Azo Dyes Based on 2,4-Dihydroxybenzophenone - Bharat C. Dixit; Hitendra M. Patel; Dhirubhai J. Desai; Ritu B. Dixit (E-Journal of Chemistry)
Novel acid azo and mordent acid azo dyes have been prepared by the coupling of diazo solution of different aminonaphthol sulphonic acids and aromatic amino acids with 2,4-dihydroxybenzophenone. The resultant dyes were characterized by elemental analysis as well as IR and 1H NMR spectral studies. The UV-visible spectral data have also been discussed in terms of structure property relationship. The dyeing assessments of all the dyes were evaluated on wool and silk textile fibers. The dyeing of chrome pretreated wool and silk have also been monitored. The result shows that better hue was obtained on mordented fiber. Results of bactericidal studies of chrome pretreated fibers revealed that the toxicity of mordented dyes against bacteria is fairly good. Dyeing on wool and silk fibers resulted in yellowish pink to reddish brown colourations having excellent light fastness and washing fastness.